G protein-coupled receptor 183 mediates the sensitization of Burkitt lymphoma tumors to CD47 immune checkpoint blockade by anti-CD20/PI3Kδi dual therapy - Ribeiro, Marcelo Lima; Profitós-Pelejà, Núria; Santos, Juliana Carvalho; Blecua, Pedro; Reyes-Garau, Diana; Armengol, Marc; Fernández-Serrano, Miranda; Miskin, Hari P.; Bosch, Francesc; Esteller, Manel; Normant, Emmanuel; Roué, Gael (Frontiers in Immunology, 2023)
Immunotherapy-based regimens have considerably improved the survival rate of B-cell non-Hodgkin lymphoma (B-NHL) patients in the last decades; however, most disease subtypes remain almost incurable. TG-1801, a bispecific antibody that targets CD47 selectively on CD19+ B-cells, is under clinical evaluation in relapsed/refractory (R/R) B-NHL patients either as a single-agent or in combination with ublituximab, a new generation CD20 antibody. Here, using a panel of B-NHL co-cultures, we show that TG-1801, by disrupting the CD47-SIRPa axis, potentiates anti-CD20-mediated antibody-dependent cell death (ADCC) and antibody-dependent cell phagocytosis (ADCP). This led to a remarkable and durable antitumor effect of the triplet therapy composed by TG-1801, ublituximab and the PI3Kδi umbralisib, in vitro, as well as in immune-compromised and immune-competent (CAM) xenograft models of B-NHL. Transcriptomic analysis also uncovered the upregulation of the G protein-coupled and inflammatory receptor, GPR183, as a crucial event associated with the efficacy of the triplet combination. Genetic depletion and pharmacological inhibition of GPR183 impaired ADCP initiation, cytoskeleton remodeling, and cell migration in 2D and 3D spheroid B-NHL co-cultures, and disrupted macrophage-mediated control of tumour growth in B-NHL CAM xenografts. Altogether, our results support a crucial role for GPR183 in the recognition and elimination of malignant B cells upon concomitant targeting of CD20, CD47, and PI3Kδ, and warrant further clinical evaluation of this triplet regimen in B-NHL.